Spirituality and the healthy mind : science, therapy, and the need for personal meaning - Galanter, Marc (Oxford University Press, 2005)
I. WHAT IS SPIRITUALITY?. 1. Spirituality Emerges. 2. A Psychological Perspective. 3. Spirituality and the Brain. II. THE IMPACT OF CULTURE. 4. The Apparent Conflict. 5. Problems With Spirituality. 6. When Something Is Missing. III. VARIETIES OF SPIRITUAL EXPERIENCE. 7. Christian Psychiatry. 8. Spirituality in India. 9. Liberal Islam. 10. Hospital Chaplaincy: Confronting Illness and Death. IV. SPIRITUAL RECOVERY MOVEMENTS. 11. Alternative Medicine. 12. Alcoholics Anonymous. V. THERAPY OF A DIFFERENT KIND. 13. 14. 15. 16.